2020
DOI: 10.1245/s10434-020-08427-4
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Radiographic Effects of Preoperative Chemotherapy and (Chemo)Radiation on Tumor Anatomy in Patients with Localized Pancreatic Cancer

Abstract: Background. The incidence and magnitude of indicators of radiographic response of pancreatic cancer to systemic chemotherapy and (chemo)radiation administered prior to anticipated pancreatectomy are unclear. Methods. Sequential computed tomography scans of 226 patients with localized pancreatic cancer who received chemotherapy consisting of 5-fluorouracil, leucovorin, oxaliplatin, and irinotecan (FOLFIRINOX) or gemcitabine and nanoparticle albumin-bound paclitaxel (GA) with or without (chemo)radiation and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…In a previous study with review of The National Cancer Data Base, it was demonstrated that the addition of radiotherapy to neoadjuvant chemotherapy was associated with higher downstaging and complete pathologic response rates than chemotherapy alone (23). Additionally, there was about 6.0-14.4% downstaging rate after chemoradiotherapy for LAPC (23)(24)(25), which was similar to that (9.3%) in our study. Nevertheless, chemoradiation did not confer a survival benefit compared with chemotherapy alone (23).…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study with review of The National Cancer Data Base, it was demonstrated that the addition of radiotherapy to neoadjuvant chemotherapy was associated with higher downstaging and complete pathologic response rates than chemotherapy alone (23). Additionally, there was about 6.0-14.4% downstaging rate after chemoradiotherapy for LAPC (23)(24)(25), which was similar to that (9.3%) in our study. Nevertheless, chemoradiation did not confer a survival benefit compared with chemotherapy alone (23).…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study with review of The National Cancer Data Base, it was demonstrated that the addition of radiotherapy to neoadjuvant chemotherapy was associated with higher downstaging and complete pathologic response rates than chemotherapy alone [23]. Additionally, there was about 6.0-14.4% downstaging rate after chemoradiotherapy for LAPC [23][24][25], which was similar with that (9.3%) in our study. Nevertheless, chemoradiation did not confer a survival bene t compared with chemotherapy alone [23].…”
Section: Discussionsupporting
confidence: 89%
“…FOLFIRINOX treatment often leads to a stabilization of the disease, or partial response occurs in a minority of the PDAC patients, while others do not respond by showing disease progression during treatment ( 6 ). However, even among the responders, most patients develop rapid therapy resistance, resulting in disease progression after treatment.…”
Section: Introductionmentioning
confidence: 99%